2011
DOI: 10.4297/najms.2011.3152
|View full text |Cite
|
Sign up to set email alerts
|

The use of C-reactive protein in predicting bacterial co-Infection in children with bronchiolitis

Abstract: Background:Bronchiolitis is a potentially life-threatening respiratory illness commonly affecting children who are less than two years of age. Patients with viral lower respiratory tract infection are at risk for co-bacterial infection.Aim:The aim of our study was to evaluate the use of C-reactive protein (CRP) in predicting bacterial co-infection in patients hospitalized for bronchiolitis and to correlate the results with the use of antibiotics.Patients and Methods:This is a prospective study that included pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 35 publications
3
27
0
1
Order By: Relevance
“…[2120] As a sepsis marker in the neonatus, procalcitonin is better than C-Reactive Protein (CRP);[21] however, CRP can be used as a marker for bacterial co-infection in the viral-induced bronchiolitis infant populations. [22]…”
Section: Discussionmentioning
confidence: 99%
“…[2120] As a sepsis marker in the neonatus, procalcitonin is better than C-Reactive Protein (CRP);[21] however, CRP can be used as a marker for bacterial co-infection in the viral-induced bronchiolitis infant populations. [22]…”
Section: Discussionmentioning
confidence: 99%
“…Gan and colleagues aggregated data from five cross-sectional studies and estimated an average mean increase in serum CRP of 1.85 mg/L in individuals with stable COPD [9]. There were similar results in the study conducted by Fares M et al [10]. They showed that CRP level >1.1mg/L in infants with bronchiolitis.…”
Section: Discussionmentioning
confidence: 61%
“…Several predictive models had reports consistently the chest indrawing as predictive of prolonged LOS that is which is biologically plausible and expected due that this sign also is a universal marker of severity of the disease, as well as the presence of underlying conditions (congenital heart disease, chronic lung conditions, immunocompromised states) (3,(6)(7)(8)(20)(21)(22) or C-reactive protein (CRP) as a biomarker of severity and bacterial co-infection in patients hospitalized for bronchiolitis (23)(24)(25) Our study has limitations. First, since this study was based on medical records review, we cannot include other variables such as environmental pollution and genetic factors, and residual confounding cannot be excluded.…”
Section: Discussionmentioning
confidence: 92%